Effect of Anise Seeds (Pimpinella anisum) Oil Extract on Some Fertility Parameters in Albino Male Mice - Weli , Sardar M.; Hama, Abdullah A.; Mohammed, Othman A.; Salih, Sabiha S.; Ali, Fatimah M.; Shareef, Osama H. (Iraqi Journal of Science, 2024)
Anise is an aromatic plant which is used in traditional medicine and pharmaceutical industry. The main components of anise seed are anise alcohol, p-anisaldehyde, estragol, acetophenone, limonene and pinene, while the volatile oil found in anise is anethole. The antioxidant, antimicrobial, anticonvulsant and analgesic properties of anise seeds and oil have been confirmed by various studies. The current study was designed to study the effects of oral administration of anise oil on the reproductive capacity of adult male mice by examining certain physiological parameters such as measuring the serum testosterone level, counting the number of sperm, sperm motility and abnormal sperm morphology. A total of 36 male mice were used and randomly divided into three equal groups. Group1 received corn oil (control), T1 received anise oil in a dose of 0.043 gm/kg B.wt , and T2 received anise oil in a dose of 0.086 gm/kg B.Wt orally. The above mentioned parameters were examined at the end of three weeks of administration for six animals of each group. As well as, the examinations were repeated at the end of six weeks of administration for the rest of the animals. The results exhibited that treatment with anise oil led to a significant increase in the level of testosterone, sperm count and motility. Furthermore, abnormal morphology of the sperms decreased significantly. In conclusion, it can be said that the administered doses of anise oil could have led to improve the fertility in male mice.